Understanding the complexity of migrant smuggling: the 'smuggling spectrum' as a comprehensive analytical framework. (22nd March 2021) - Alagna, Federico
Migrant smuggling has been conceptualised in many different ways and from many different perspectives. Over the last 15 years, the rise of more critical studies, which challenged a dominant security-oriented and policy-driven framework, has been extremely important, and it contributed to generating new understandings of the phenomenon. Acknowledging the validity of these multiple approaches and the need for common analytical grounds, I try to offer a broadly applicable analytical framework in order to understand and compare the different empirical manifestations of smuggling and the connected policy responses. To do so, migrant smuggling is firstly unpacked, focusing on its two main components - smugglers and smuggled migrants - and identifying their characteristic elements. The latter are, in turn, brought back together and conceptualised as an area of complexity: the 'smuggling spectrum'. This enables a flexible and comprehensive understanding of smuggling, acknowledging the existing complexity and yet making it analytically manageable.